Modelling and Analysis of Forest Fire in Portugal - Part I - Silva, Giovani Loiola (2014)
In the last decades forest fires became a serious problem in Portugal due to different issues such a climatic characteristics and nature of Portuguese forest. In order to analyze forest data, we use generalized linear models for modeling the proportion of burned forest area. Our goal is to find out fire risk factors that influence that proportion of burned area and what may make a forest type susceptible or resistant to fire. Then, we analyze forest fire data in Portugal during 1990-1994 through frequentist and Bayesian approaches.